The Effectiveness of Pengembangan Usaha Pangan Masyarakat (PUPM) as an Effort to Stabilize Food Commodity Prices (Study at the Ministry of Agriculture the Republic of Indonesia, Food Security Agency) - Dwiko Rynoza Nur Rachman; Ali Roziqin; Achmad Apriyanto Romadhan (Budapest International Research and Critics University, 2022)
Community Food Business Development Activities or (PUPM) is a community empowerment program from community food business institutions (LUPM) consisting of a combination of farmer groups (Gapoktan), farmer groups (Poktan), community business institutions engaged in food and industry/producers/ distributor of food ingredients as to serve Indonesian Farmer Shops (TTI) in terms of providing staple food and strategies for the community. The purpose of this PUPM is as an effort to maintain prices both at the farmer/producer level and at the consumer level. The writing in this study uses a qualitative research type with a descriptive approach. The use of qualitative research aims to understand a problem based on the preparation of a complex and comprehensive picture according to a detailed view. The results of this study if the authors look at its effectiveness in terms of stabilizing food commodity prices, it has been going well but not optimal in its application. Regarding the performance of the implementation of PUPM-TTI activities in 2020, seen from the total volume of supply of food commodities to TTI/TTIC nationally, reaching 46,128 tons or 104.27% of the target of 44,128 tons. This means that in this case, PUPM's performance in terms of supplying food commodities to TTI/TTIC has exceeded the target day to be achieved.